2007
DOI: 10.1016/j.jmb.2006.10.047
|View full text |Cite
|
Sign up to set email alerts
|

The Folding Pathway of T4 Lysozyme: The High-resolution Structure and Folding of a Hidden Intermediate

Abstract: Folding intermediates have been detected and characterized for many proteins. However, their structures at atomic resolution have only been determined for two small single domain proteins: Rdapocytochrome b 562 and engrailed homeo domain. T4 lysozyme has two easily distinguishable but energetically coupled domains: the N-and C-terminal domains. An early native-state hydrogen exchange experiment identified an intermediate with the C-terminal domain folded and the Nterminal domain unfolded. We have used a native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
2
32
1
Order By: Relevance
“…In fact, in some experiments, mutations were intentionally introduced to stabilize various folding intermediates to facilitate their characterization [84,85]. In one case, swapping certain hydrophobic core residues between two related proteins could also swap the associated folding intermediates [86].…”
Section: Biophysical Consequences Of Protein Mutations 21 Mutationamentioning
confidence: 99%
“…In fact, in some experiments, mutations were intentionally introduced to stabilize various folding intermediates to facilitate their characterization [84,85]. In one case, swapping certain hydrophobic core residues between two related proteins could also swap the associated folding intermediates [86].…”
Section: Biophysical Consequences Of Protein Mutations 21 Mutationamentioning
confidence: 99%
“…T4L is exploited as a model system in development of SDSL technology because of the extensive data base of WTand mutant crystal structures, including many bearing the R1 side chain (19,20,23,24), as well as solution NMR (30)(31)(32) and hydrogen exchange data (33)(34)(35). The enzyme consists of two independently folding subdomains (N and C).…”
Section: Resultsmentioning
confidence: 99%
“…The much smaller ΔV o compared to that of 118R1 suggests that the equilibrium observed is not that for the N ⇌ U equilibrium, but rather an N ⇌ I equilibrium, where I is an intermediate with incomplete unfolding. It is known that the stability of the N subdomain is lower than that for the C subdomain (38) and that intermediate folding states (I) exist for T4L in which the N and C terminal subdomains are unfolded and folded, respectively (30,33,38,39). The broad transition region of the CD-detected urea denaturation curve of 46R1 also suggests a partially unfolded intermediate state (SI Text).…”
Section: Urea] >5 M (Si Text) the Mutant Is Destabilizedmentioning
confidence: 99%
“…In recent years, it has been found that even for the conventionally observed small two-state proteins (~100 amino acids or less) there exist partially unfolded intermediates on the folding pathways. These intermediates are generally undetectable in kinetic folding experiments [8,116,[164][165][166][167][168] and, therefore, are called "hidden intermediates". In addition, mounting evidence has indicated that the intermediate states formed during protein folding and unfolding may have significant roles in protein functions (Fig.…”
Section: Protein Intermediate Statesmentioning
confidence: 99%